Дослідження підходів до візуалізації і структуризації атак у контексті моделювання дій зловмисників в інфокомунікаційній мережі - Фукс, М. А. (ХНУРЕ, 2025)
This work is devoted to analyzing modern approaches to representing attacks for the purpose of modeling adversarial actions and assessing system security. It is vital to adopt robust models for analyzing potential scenarios, identifying system vulnerabilities, and effectively prioritizing countermeasures. This work focuses on three primary approaches to representing attacks: attack trees, attack graphs, and matrix-based models. By examining each model’s capabilities, the paper highlights the importance of selecting or combining appropriate approaches to gain insights into attacker behavior and enhance security posture.
Keywords: моделювання дій зловмисників; візуалізація атак